Adenoid basal cell carcinoma: A rare variant and a diagnostic dilemma - Neha Sethi; Anjali Sharma; Chaitali Singh; Kirti Pandia; Anil Gupta (Wolters Kluwer Medknow Publications, 2021)
Basal cell carcinoma (BCC) constitutes the most common malignancy of the skin, accounting around 70% of all skin malignancies, especially in sun-exposed areas. The adenoid variant is a very uncommon subtype which accounts for approximately 1.3% of all BCCs. A 65-year-old male presented with ulcer and swelling on the left side of the nose and cheek with rolled borders for the past 2 years. Based on the histopathology and immunohistochemistry, the diagnosis of the adenoid type of BCC was made. One should be aware of its close mimics such as primary cutaneous adenoid cystic carcinoma before diagnosing adenoid BCC as they differ in prognosis and treatment modalities.